2004
DOI: 10.1021/om049061m
|View full text |Cite
|
Sign up to set email alerts
|

Decarbonylation of Acetone and Carbonate at a Pincer-Ligated Ru Center

Abstract: A Ru center ligated by a pincer bis(o-phosphinoaryl)amine (PNP) ligand in (PNP)RuH(H2) is sufficiently electron rich to break C−O and C−C bonds, resulting in the ultimate decarbonylation of hydrocarbonate and acetone, respectively, to give (PNP)RuH(CO). The decarbonylation of acetone is accompanied by hydrogenolysis of the C−C bonds to produce methane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 47 publications
0
32
0
Order By: Relevance
“…It was also reported that Ru hydrides (with diphosphinoamine (PNP) ligands) promoted the decarbonylation of acetone affording methane and Ru(CO). [14] If 1,3-dihydroxyacetone followed the same reaction path, that is, if only the C(2) of glycerol was involved in the reaction with the Ru metal centre, we should detect methanol or formaldehyde in the reaction medium. We did not detect such species, therefore, we could conclude that the carbonyl source could not be the C(2), but one of the terminal ÀCH 2 OH moieties.…”
Section: Resultsmentioning
confidence: 99%
“…It was also reported that Ru hydrides (with diphosphinoamine (PNP) ligands) promoted the decarbonylation of acetone affording methane and Ru(CO). [14] If 1,3-dihydroxyacetone followed the same reaction path, that is, if only the C(2) of glycerol was involved in the reaction with the Ru metal centre, we should detect methanol or formaldehyde in the reaction medium. We did not detect such species, therefore, we could conclude that the carbonyl source could not be the C(2), but one of the terminal ÀCH 2 OH moieties.…”
Section: Resultsmentioning
confidence: 99%
“…22 Moreover, Foxman and Ozerov reported the CO functionalisation of a PNP type ruthenium pincer hydride complex obtained through decarbonylation of acetone. 23 Based on previous reports by Milstein et al, we accordingly assume that a cis-[RuH 2 (CO)(Me-PNP)] complex is generated in the first step, which undergoes then, despite the high trans influence of the hydride ligands, a rapid cistrans isomerisation into the thermodynamically more stable and sterically more favourable trans isomer 3. [34][35][36][37] In the 13 C-NMR spectrum, the CO signal was found at 210.8 ppm (t, 2 J CP = 13.2 Hz), which was further confirmed by decarbonylation reactions of 13 C labeled ethanol (ESI, Fig.…”
Section: Catalytic Oxidation Of Alcoholsmentioning
confidence: 99%
“…Separately, complex 3 was used for catalytic alcohol dehydrogenation reactions in water. Based on achievements in earlier reports, 12,13,[21][22][23][24][25] we investigated the decarbonylation behaviour of a similar PNP pincer based ruthenium complex [Ru(H 2 )H(PNP)] 5. Complex 5 can be transformed into a carbonyl complex [RuH(CO)(PNP)] 6 and converted into a trans dihydride complex [RuH 2 (CO)(H-PNP)] 7 under a hydrogen atmosphere (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It thus appears that both methanol and primary alcohols such as ethanol should decarbonylate similarly well. In contrast, the secondary alcohol i PrOH (or more specifically, its primary dehydrogenation product, acetone) is rather more resistant to decarbonylation,27 which makes it a popular substrate for model studies of alcohol dehydrogenation 3b,c. We were thus expecting rather high barriers on pathways F and G with 2‐propanol.…”
Section: Resultsmentioning
confidence: 99%